PH CONTROL ON OXYGEN ISOTOPIC COMPOSITION OF SYMBIOTIC CORALS - Rollion-Bard C.; Chaussidon M.; France-Lanord C. (My University, 2003)
Boron, carbon and oxygen isotopic compositions were determined at the micrometre scale by high-resolution ion microprobe in a sample of modern coral (massive hermatypic coral, Porites lutea). The ion probe data show for B and O much larger isotopic variations at the micrometre scale than those measured at the millimetre scale by conventional techniques: δ18OPDB values range from -10.6+/-0.9%% to -0.2+/-0.5%% and δ11B values range from +18.6+/-1.5%% to +30.6+/-1.6%%. By contrast, δ13C values show the same range of variations, from -4.6+/-0.65%% to -2.2+/-0.67%% at the micrometre and millimetre scales. The range of δ11B values indicates that significant pH variations, from ~7.1 to ~9.0, are present at the sites of calcification. The largest δ18O variations correspond to the highest δ11B values, i.e. to the highest pHs. This measurement of pH allows modelling the oxygen isotopic fractionation occurring during aragonite precipitation. Taking into account the rate of O isotopic equilibrium between dissolved carbonate species (H2CO3, HCO3- and CO32-) and water via the two reactions of hydration and hydroxylation, the full range of δ18O values measured at the micrometre scale can be modelled for residence times of dissolved carbonates in the calcifying fluid ranging between ~1 h and at maximum ~12 h. The pH controls the δ18O of the growing carbonate through the relative fractions of dissolved carbonate species and through the kinetics of their isotopic equilibration with water via hydration and hydroxylation. The so-called 'vital effect' systematically observed for δ18O in corals can thus be understood as representing an average of rapid pH variations due to coral biology during coral growth. Selectively measuring δ18O values in the zones of coral skeletons that have low δ11B values (i.e. formed at low pH) should significantly improve the quality of palaeoclimatic reconstructions based on δ18O values.
Keywords: CORAL; ION MICROPROBE; VITAL EFFECT; δ18O; δ13C; δ11B; PH